2018
DOI: 10.1177/0892705718780195
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide 6 and high molecular weight phenol novolac blend having excellent mechanical properties in humid conditions

Abstract: Polymer blends of polyamide 6 (PA6) and phenol novolac (PN) were prepared by melt mixing. Up to 30 wt% of high molecular weight PN (HPN) or low molecular weight PN (LPN) was blended with PA6, and the physical and mechanical properties were examined. The water absorption of PA6 is inhibited by PN, and this effect is independent of the molecular weight of PN. PA6 and PN are miscible, and their blends show a single glass transition temperature ( T g) that is higher than that of PA6. HPN can enhance the T g of PA6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In fact, exposure to corrosive fluids significantly compromises the load carrying capacity, due to the lower mechanical properties of the matrix and the lower fibre/matrix bond strength [11,13,53]. Studies developed by Hirai et al [56] showed, for example, that PA6 is easily plasticized when subjected to wet conditions, which significantly affects its mechanical performance. Other evidence from Table 3 and Figure 3 is the higher effect of the hostile environments on the laminates with fibres at 0 • (74.8% for HCl and 227.2% for NaCl solutions) than in the other orientations.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, exposure to corrosive fluids significantly compromises the load carrying capacity, due to the lower mechanical properties of the matrix and the lower fibre/matrix bond strength [11,13,53]. Studies developed by Hirai et al [56] showed, for example, that PA6 is easily plasticized when subjected to wet conditions, which significantly affects its mechanical performance. Other evidence from Table 3 and Figure 3 is the higher effect of the hostile environments on the laminates with fibres at 0 • (74.8% for HCl and 227.2% for NaCl solutions) than in the other orientations.…”
Section: Resultsmentioning
confidence: 99%
“…PA6/PET/PN20 also displayed high moduli in the glassy state, owing to the high T g of PA6 in PA6/PET/PN20, which is above room temperature. However, embrittlement, a disadvantage of excess PN loading to PA6, 20 was observed.…”
Section: Flexural Test At Water-absorbed Statementioning
confidence: 97%
“…Various polymer blends have been proposed to improve the mechanical properties of PA6 under humid and high-temperature conditions. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Owing to the small mixing enthalpy of macromolecules, almost all polymer combinations are immiscible 5 and thus, previous studies have mainly conducted PA6 polymer blending with immiscible components. [7][8][9][10][11][12][13][14] Blending high-T g polymers, such as poly(phenylene sulde), 7,8 poly(phenylene oxide), [9][10][11] and polycarbonate (PC) [12][13][14] with PA6 are representative approaches to increase the PA6 stiffness at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations